2022
DOI: 10.1108/oir-02-2021-0101
|View full text |Cite
|
Sign up to set email alerts
|

Information discernment and online reading behaviour: an experiment

Abstract: PurposeThis paper intends to explore the relationship between participants' eye fixations (a measure of attention) and durations (a measure of concentration) on areas of interest within a range of online articles and their levels of information discernment (a sub-process of information literacy characterising how participants make judgements about information).Design/methodology/approachEye-tracking equipment was used as a proxy measure for reading behaviour by recording eye-fixations, dwell times and regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Pointon et al. (2022) showed that the level of information recognition is related to attention: the lower the information recognition ability, the lower the attention of the individual, the less curiosity in recognizing information, the higher the tendency to ignore factual information and the greater the lack of systematic scanning movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pointon et al. (2022) showed that the level of information recognition is related to attention: the lower the information recognition ability, the lower the attention of the individual, the less curiosity in recognizing information, the higher the tendency to ignore factual information and the greater the lack of systematic scanning movements.…”
Section: Discussionmentioning
confidence: 99%
“…H1, H9, H11 and H16 were supported (see Figure 8). Pointon et al (2022) showed that the level of information recognition is related to attention: the lower the information recognition ability, the lower the attention of the individual, the less curiosity in recognizing information, the higher the tendency to ignore factual information and the greater the lack of systematic scanning movements. This study examines how children process accessible and diagnostic information on mobile devices and the relevance of perceptual speed, associative memory and information-searching behaviors to eye movements.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Zhang et al, 2020). Message attractiveness in communication contexts refers to the appeal of a message's format and style, usually reflected through message design elements and linguistic features, such as seductive text (Pointon et al, 2023). Attractive messages capture the audience's attention and interest, leading them to directly perceive the meaning and emotion conveyed by the message without the need for deliberation (Lin et al, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 99%